2015
DOI: 10.17843/rpmesp.2015.323.1678
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de electroinmunotransferencia utilizando antígeno mix nativo purificado de líquido de cisticerco de Taenia solium para el diagnóstico de cisticercosis humana

Abstract: Objetivos. Evaluar la eficacia de la prueba electroinmunotransferencia (EITB) para la detección de cisticercosis humana utilizando antígeno mix nativo purificado de líquido de cisticerco de Taenia solium. Material y métodos. Estudio observacional de evaluación de prueba diagnóstica. El antígeno mix nativo purificado se extrajo del líquido de cisticerco de cerdos naturalmente parasitados de áreas consideradas endémicas, se evaluó y seleccionó uno de los cuatro métodos de purificación: sulfato de amonio, lecitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…45 This method integrates the high resolution of SDS-PAGE and high specicity of immunoassays; therefore, it is very suitable for the highly sensitive detection of target proteins among different complexes ( . [43][44][45][46] The chronic infection caused by Pseudomonas aeruginosa can be fatal for CF patients. Shand et al (1988) prepared a standard antigen (StAg) of Pseudomonas aeruginosa to serve as a basis for developing the IBT method with serum antibodies.…”
Section: Enzyme-linked Immunoelectrotransfer Blots (Ibts)mentioning
confidence: 99%
See 1 more Smart Citation
“…45 This method integrates the high resolution of SDS-PAGE and high specicity of immunoassays; therefore, it is very suitable for the highly sensitive detection of target proteins among different complexes ( . [43][44][45][46] The chronic infection caused by Pseudomonas aeruginosa can be fatal for CF patients. Shand et al (1988) prepared a standard antigen (StAg) of Pseudomonas aeruginosa to serve as a basis for developing the IBT method with serum antibodies.…”
Section: Enzyme-linked Immunoelectrotransfer Blots (Ibts)mentioning
confidence: 99%
“…(2015) detected human cysticercosis which utilized puried native antigen mix from cysticercus uid of Taenia solium by using ITBs techniques, and results showed that the puried native antigen mix improved the diagnostic efficiency of the IBTs test. 46…”
Section: Enzyme-linked Immunoelectrotransfer Blots (Ibts)mentioning
confidence: 99%
“…El pool de sueros positivos a la tres parasitosis permitió reconocer 13 antígenos de excreción/secreción, ocho de C. cellulosae glicoproteínas para cisticercosis (GPC: 35,31, 24,23,18,17,14,13); tres de E. granulosus (GPH: 21,16,8), y dos de F. hepática (GPF:23 y 17 KDa).…”
Section: Resultsunclassified
“…El diagnóstico de la cisticercosis, hidatidosis y fascioliasis por Western Blot empleando kits individuales tienen sensibilidades de 91 (23) , 80 (24) y 95% (25) respectivamente y una especificidad del 100%, pero usar dos o tres kits en zonas endémicas de multiparasitismo dificulta el trabajo del analista, requiere mayor tiempo para el procesamiento y entrega de resultados, además de un mayor costo para el paciente. Este estudio demuestra que se puede elaborar un Western Blot múltiple para diagnosticar parasitosis con la misma eficiencia que los kits individuales.…”
Section: Discussionunclassified
See 1 more Smart Citation